2001
DOI: 10.1002/app.1567
|View full text |Cite
|
Sign up to set email alerts
|

Impact behavior of sawdust/recycled–PP composites

Abstract: ABSTRACT:The instrumented Izod and Charpy tests were performed on the sawdustpolypropylene (PP) composites to study the nature of impact resistance in the thermoplastic wood composites. The notched Izod strength was found to increase with filler content in composites containing the Maleic-anhydride-grafted PP (MAPP) additive. The Izod strength even exceeds that of the neat matrix resin at higher filler contents, indicating a methodology for applying the recycled PP and also for reinforcing the thermoplastics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…This feature can be attributed to the elastic characteristics of particles or refined fibers. This finding is in line with the findings of various studies this issue (Li et al 2001;Jayaraman and Bhattacharyya 2004;Chaharmahali et al 2008).…”
Section: Tensile Modulussupporting
confidence: 93%
“…This feature can be attributed to the elastic characteristics of particles or refined fibers. This finding is in line with the findings of various studies this issue (Li et al 2001;Jayaraman and Bhattacharyya 2004;Chaharmahali et al 2008).…”
Section: Tensile Modulussupporting
confidence: 93%
“…Several theories of the dependence of composite properties on filler volume fraction F and geometry have been investigated. 23,[35][36][37] In a simple model Nicolais and Narkis 35 developed a geometric model for the tensile strength s of a composite with uniformly distributed spherical filler particles of equal radius…”
Section: Tensile Properties Of Pp/scb Compositesmentioning
confidence: 99%
“…This situation makes wood flour a competitive substitute for the cellulose fibers, especially when extrusion compounding and injection molding are used as processing methods. 6 Chen et al 7,8 prepared a series of maleated polypropylene (MPP) compatibilized polypropylene (PP)/ bamboo fiber composites with higher tensile strength, lower density, and lower cost. The results showed that the tensile strength and the stiffness of bamboo fiberreinforced PP composites were higher than those of the commercial wood pulp composite that was widely used in making office furniture.…”
Section: Introductionmentioning
confidence: 99%